Percepção ambiental da população residente no entorno de dois parques naturais municipais de Sinop, Mato Grosso - Borba, Cleonice Maria (2023)
The conversion of natural habitats into economically active areas has caused major changes in tropical landscapes, especially in humid forests, which have lost territory, mainly due to the expansion of the agricultural and livestock frontier. This process of advancing the agricultural frontier over the tropical forest results in changes in the landscape, with reduced connectivity between habitats and an increase in the number of fragments, inserted in an unfavorable matrix that, due to isolation, makes it difficult for species to disperse and, consequently, the gene flow of these populations. In the midst of the urban matrix, urban forest fragments are remnants of natural vegetation, which correspond to parks, reserves and small patches of forests on private properties. In these urban ecosystems, despite the high anthropic pressure and not having the possibility of connection with other forests, these fragments play a strong ecological and social role as it is recognized that the presence of these forests constitute refuge for many species, functioning as microclimatic and indispensable thermal regulators to the quality of life of the population and act positively in the energy efficiency of the buildings that surround them. There are also neighborhood groups that can develop an affective link (topophilia) or disaffection and aversion (topophobia) in relation to these forest landscapes. Thus, this study aimed to evaluate the environmental perception of residents who live around forest fragments in the urban perimeter of the municipality of Sinop, Mato Grosso. The study was carried out with residents around two Conservation Units in the urban perimeter of Sinop. Information on the perceptions of residents living in the urban surroundings of these forest fragments were obtained through an objective questionnaire, prepared based on the Linkert scale, that is, aiming to understand the degree of perception of respondents on a scale ranging from “I totally agree” to “I totally agree”. I totally disagree”, totaling 30 respondents per area. In the end, 60 residents were interviewed. With this study we can understand how the environmental components present in the urban green areas of Sinop are significant to the population, who aim for their conservation and maintenance, as well as through this study we identify environmental problems associated with the urban green areas, according to the population's perception, indicating possible interventions that allow its mitigation or solution.